'Girls don't play soccer': children policing gender on the playground in a township primary school in South Africa. Issue 4 (7th June 2017) - Mayeza, Emmanuel
ABSTRACT: This paper is based on an ethnographic study conducted between 2012 and 2014 with a group of 64 boys and girls aged 6–10, all attending the same township primary school in South Africa. The paper explores how the young children construct gender 'boundaries' and 'police' gender 'transgressions' on the school playground during break-time. The findings illustrate the ways in which these young boys and girls learn to 'do' gender through practices of inclusion, exclusion and 'policing' during play. The findings challenge dominant teacher constructions of the playground as a 'free space' and demonstrate how the playground operates as a site of learning gender through forms of 'policing' that involve boys bullying girls and boys who do not conform to gender norms. The findings raise implications for the development of curriculum material and teaching practices that would assist primary schoolteachers to reflect more deeply on young learners' personal experiences and perspectives around gender and play.